Factors associated with lack of treatment adherence in glaucoma patients - Larco, Andrea (2020)
Objective. Was to determine the factors associated with the lack of adherence to ophthalmological treatment in patients with glaucoma, at a private clinic. Methods. Observational, analytical and crosssectional design. The sample consisted of 106 patients with a previous diagnosis of glaucoma. The statistical analysis was carried out with STATAv.16., the Student’s t test, the Chi square test and the logistic regression analysis were performed with a level of significance of 5%. Results. The average age of the patients was 66,6 ± 13,8 years, the majority were women (59,43%), from the coast (62,26%), with a high school degree education (38,68). The frequency of poor adherence to ophthalmological treatment was 69,81% (n = 74). The multivariate logistic regression analysis revealed that accessibility to medications (OR = 0,10; 95% CI = 0,03-0,32) and compliance with the time of medication (OR = 0,09; 95% CI = 0,02- 0,33) represent protective factors of poor adherence to treatment, while the interruption of medication due to feeling good in health (OR = 9,23; 95% CI = 1,08-78,52), needing help to place the drops (OR = 2,61; 95% CI = 1,10-6,20) and stopping treatment if help is not found (OR = 4,43; 95% CI = 1,19-16,25) represent risk factors for poor adherence to ophthalmological treatment. Conclusion. Glaucoma patients without access to medications, who fail to adhere to their medication schedule, who interrupt their medication because they feel good, who need help in their care and cannot find help are more prone to poor adherence to ophthalmological treatment.